Usefulness of CSF Biomarkers in Predicting the Progression of Amnesic and Nonamnesic Mild Cognitive Impairment to Alzheimer’s Disease - Ortega, Ricard L.; Dakterzada, Farida; Arias, Alfonso; Blasco, Ester; Naudí, Alba; Garcia, Francisco P.; Piñol-Ripoll, Gerard (Current Aging Science, 2019)
Objective: The aim of this study was to investigate the usefulness of Alzheimer’s disease Cerebrospinal Fluid (CSF) biomarkers in predicting the progression to dementia in patients with Mild Cognitive Impairment (MCI). Methods: One hundred and thirteen patients were consecutively recruited from April 2012 to April 2014. Measurement of CSF biomarkers (amyloid-β42 (Aβ42), total tau (t-tau) and phosphorylated tau (p-tau)) and a neuropsychological evaluation were performed for all patients. We categorized patients with MCI as A+A- and N+N- based on the presence/absence of amyloid pathology and neurodegeneration, respectively. Results: Of 72 patients with MCI, 26 (36%) progressed to dementia. These patients had lower CSF Aβ42 levels and higher p-tau and t-tau levels at baseline. The proportion that progressed to dementia was 14.3% (2/14), 36.8% (7/19), 66.7% (4/6) and 75% (12/16) in the A-N-, A+N-, A-N+ (SNAP), and A+N+ patients, respectively (p < 0.05). There were significant differences in the probability of progression from amnestic MCI (aMCI) to AD between the A+N+ and A-N- patients (OR = 8.1, 95% CI 1.5-42.3, p = 0.001) but not between SNAP (OR = 7.3, 95% CI 0.9-61, p = 0.02) or A+N- (OR = 2.1, 95% CI 0.4 to 10.4, p = 0.15) patients compared to the A-N- subgroup. None of the biomarker profiles of the subgroups predicted the time until the progression to AD. Conclusion: The use of CSF AD biomarkers in clinical practice improves the certainty of diagnosis and prognosis of patients, especially in patients in the prodromal phase or in patients with atypical presentations.
Keywords: Alzheimer' s disease